1998
DOI: 10.1007/s002689900446
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Calcium Homeostasis after Renal Transplantation

Abstract: Nineteen consecutive patients receiving renal transplants underwent prospective evaluation of their calcium homeostasis for 1 year after transplantation to characterize indices of hyperparathyroidism (HPT) amelioration. All but one underwent dialysis, and six had vitamin D supplementation before grafting. The rapid falls in serum creatinine concentrations and increased creatinine clearances the first weeks after grafting were accompanied by rapidly reversed hypercalcemia and hypermagnesemia, induced hypophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…PTH levels immediately (≤2 weeks) after surgery, however, were variable with 2 studies reporting decreases [11, 17] and 2 reporting increases [10, 13]. The effect of kidney transplant on PTH levels occurred primarily during the first 6 months and only minimal changes were noted after this point.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PTH levels immediately (≤2 weeks) after surgery, however, were variable with 2 studies reporting decreases [11, 17] and 2 reporting increases [10, 13]. The effect of kidney transplant on PTH levels occurred primarily during the first 6 months and only minimal changes were noted after this point.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of kidney transplant on PTH levels occurred primarily during the first 6 months and only minimal changes were noted after this point. Between post-transplant months 6 and 12, additional decreases in PTH were reported in 3 studies (range 8–27%; median 16%; 192 subjects) [14, 16, 20] and increases noted in 6 (range 5–38%; median 8.7%; 212 subjects) [11, 12,17,18,19, 21]. Two studies reported PTH levels between post-transplant months 12 and 24; both studies noted minimal change (<3%) [12, 21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As kidney function recovers after KT, the accumulated FGF-23 and PTH exaggerate renal tubular Pi leak, leading to Pi depletion (4,5). Serum Pi gradually increases, reaching the normal limits within 12 months in association with the decline in PTH and FGF-23 toward baseline (1,4).…”
Section: Introductionmentioning
confidence: 99%